Implementasi Teknologi Produksi dan Kemasan pada Usaha Kemplang Ikan di Pulau Panjang, Bangka Selatan - Ardiansyah Kurniawan; Tiara Puspa Anjani; Denny Saputra; Zindi Sapeti Sari; Andika Saputra; Uswatun Khasana; Zeli Zuyadi; Inas Razzaqu Alam; Noviar Kandiaz; Eva Lestari (Politeknik Piksi Ganesha Indonesia, 2023)
Panjang Island, one of the islands in the Bangka Belitung Archipelago Province, has a significant capture fishery potential. The fishermen's wives manage by-products from fish catches as raw materials for fish kemplang production. However, the development of the kemplang fish business has not been optimal with various obstacles. University of Bangka Belitung team is trying to help kemplang processors on Panjang Island improve the production and packaging. Empowerment is carried out through socialization and training. Socialization was carried out to convey good manufacturing practice (GMP) and sanitation in kemplang production, while training was conducted on the use of cutting tools and packaging of kemplang products. The kemplang cutter can adjust the thickness and uniformity of the kemplang slices. Standing pouch packaging and using a sealer can increase the quality of kemplang's shelf life and provide an attractive appearance. Implementing production and packaging technology can be accepted by business actors making fish kemplang on Panjang Island.